Analysis case of Performance during front handspring front tuck on gymnasts in floor exercise - .Qasim Mohammed Sayah (University of Basrah, 2024)
The purpose of this study is to compare and analyze time of elapsed phase-by-phase, center-mass, changes in angles joints and, angular velocities at each phase of Front handspring front tuck performed by four gymnasts from the Iraqi National Gymnastics Team. In addition to provide quantitative data highlighting the strengths and weaknesses of gymnasts to enable a more stable landing technique.The results show that, for the performance of front handspring front tuck, a lot of time; it was enough to turn the player's movement in the air,shortening the time required until the hands are released.A short horizontal displacement was shown by folding the body to obtain a sufficient amount of turn to the maximum height vertical displacement continuously increased to the front air flight to increase the sufficient amount of rotation.The hips are flexed until the hand stitches, while the handspring are extended to the maximum extent until the jump. In order to obtain a sufficient amount of rotation after taking off from the ground.the shoulder angular velocity was fast during the hops step, and the slow angular velocity of the shoulder until the take-off after the hand spring